Is obesity a risk factor for Clostridium difficile infection?. Issue 1 (January 2015) - Punni, Emma; Pula, Jaime L.; Asslo, Fady; Baddoura, Walid; DeBari, Vincent A.
Summary Background The epidemiology of Clostridium difficile infection (CDI) has become an important area of investigation, especially in light of the global increase in both hospital-acquired (HA) and community-acquired (CA) CDI. Recently, obesity was found to be associated with CDI and was suggested to represent an independent risk factor for it. Objective We undertook a case–control study to examine obesity as an exposure for both HA and CA cases in adults (age ≥ 18 years) admitted to a tertiary, university-affiliated, acute care medical facility in the northeastern United States. Methods During the period January 2012–July 2013, we examined cross-sectional BMI data on 189 cases of CDI and 189 contemporaneous age and gender-matched controls. Results We were unable to detect a statistically significant difference between the two groups; in fact, the BMI values for both groups were substantially equivalent (cases: median = 26.5 kg/m, IQR: 22.1–32.5; controls: median = 26.0, IQR: 22.7–31.0; p = 0.696). Odds ratios (and 95% confidence intervals), evaluated at BMI of 25, 30 and 35 kg/m2, did not demonstrate statistical significance. Conclusion These data suggest that obesity, as described by BMI, may not be a risk factor for CDI in all populations.